A molecular perspective on mGluR5 regulation in the antidepressant effect of ketamine - Ola Sobhy A. Elmeseiny; Heidi Kaastrup Müller (Elsevier, 2024)
Ketamine, a non-competitive N-methyl-D-aspartate receptor (NMDAR) antagonist, has received much attention for its rapid antidepressant effects. A single administration of ketamine elicits rapid and sustained antidepressant effects in both humans and animals. Current efforts are focused on uncovering molecular mechanisms responsible for ketamine's antidepressant activity. Ketamine primarily acts via the glutamatergic pathway, and increasing evidence suggests that ketamine induces synaptic and structural plasticity through increased translation and release of neurotrophic factors, activation of mammalian target of rapamycin (mTOR), and α-amino-3-hydroxy-5-methyl-4-isoxazole propionic acid receptor (AMPAR)-mediated synaptic potentiation. However, the initial events triggering activation of intracellular signaling cascades and the mechanisms responsible for the sustained antidepressant effects of ketamine remain poorly understood. Over the last few years, it has become apparent that in addition to the fast actions of the ligand-gated AMPARs and NMDARs, metabotropic glutamate receptors (mGluRs), and particularly mGluR5, may also play a role in the antidepressant action of ketamine. Although research on mGluR5 in relation to the beneficial actions of ketamine is still in its infancy, a careful evaluation of the existing literature can identify converging trends and provide new interpretations. Here, we review the current literature on mGluR5 regulation in response to ketamine from a molecular perspective and propose a possible mechanism linking NMDAR inhibition to mGluR5 modulation.